Untreated primary hypothyroidism presenting as two rare syndromes - Sushma Save; Amoolya Lois; Richa (Indian Journal of Child Health, 2021)
The association of chronic untreated primary hypothyroidism, delayed skeletal growth, and isosexual incomplete precocious puberty together describes Van Wyk Grumbach syndrome (VWGS). Sporadic case reports of this syndrome have been reported. Laboratory investigations reveal high levels of thyroid-stimulating hormone and delayed bone growth. VWGS has seldom been reported in a case of cerebral palsy. Here, we present the cases of two girls aged 11 years and 8 years who presented to our hospital with VWGS, one of whom was a case of spastic quadriparesis cerebral palsy. They were started on thyroxine supplements and showed favorable outcomes, thus emphasizing the importance of recognizing these rare manifestations of hypothyroidism, which on treatment show reversal to the prepubertal state.